2021
DOI: 10.1108/mrr-08-2020-0536
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership in project-based organizations of Pakistan: the role of psychological empowerment and Islamic work ethics

Abstract: Purpose This study aims to examine the relationship between ethical leadership and project success directly and indirectly through psychological empowerment along with the moderating role of Islamic work ethic. Design/methodology/approach Using a time-lagged design, data were gathered from 202 employees working in project-based organizations of Pakistan. Confirmatory factor analysis confirmed the distinctiveness of variables used in the study. Findings Consistent with the cognitive evaluation theory, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…In this regard, Gyamerah et al (2022) found that benevolent leadership combined with psychological empowerment can enhance employees' creativity and their intention to stay. Mubarak et al (2022) also examined the role of ethical leadership in project management and found that ethical leadership promotes project success directly and along with psychological empowerment as well. Therefore, in the present study, it is assumed that psychological empowerment as a comprehensive intrinsic motivational mechanism can moderate the effects of ethical leadership on employee success.…”
Section: Moderating Role Of Psychological Empowermentmentioning
confidence: 99%
“…In this regard, Gyamerah et al (2022) found that benevolent leadership combined with psychological empowerment can enhance employees' creativity and their intention to stay. Mubarak et al (2022) also examined the role of ethical leadership in project management and found that ethical leadership promotes project success directly and along with psychological empowerment as well. Therefore, in the present study, it is assumed that psychological empowerment as a comprehensive intrinsic motivational mechanism can moderate the effects of ethical leadership on employee success.…”
Section: Moderating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Expressly, ethical leadership indirectly improves employee wellbeing through POS. Previous studies demonstrated that leaders exert authority or control over their work or project schedules to motivate employees in the workplace (22,51,52). Contrarily, we argue that ethical leadership is process-oriented rather than outcome-oriented.…”
Section: Discussionmentioning
confidence: 64%
“…, 2021). According to Mubarak et al. (2021) there is a direct relationship between ethical management and team integration and empowerment based on social learning.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the affective component of the project team, in addition to the resilience capacity of the project TMs, mediates the cognitive component (Pavez et al, 2021). According to Mubarak et al (2021) there is a direct relationship between ethical management and team integration and empowerment based on social learning. The study by Flavian et al (2019) linked empathy and perceived justice in the manager as antecedents to TB and trust, in turn, is an antecedent to team engagement.…”
Section: Problemsolving In Project Managementmentioning
confidence: 99%